Enabling Extreme Fast‐Charging: Challenges at the Cathode and Mitigation Strategies. Issue 46 (1st November 2022) - Tanim, Tanvir R.; Weddle, Peter J.; Yang, Zhenzhen; Colclasure, Andrew M.; Charalambous, Harry; Finegan, Donal P.; Lu, Yanying; Preefer, Molleigh; Kim, Sangwook; Allen, Jeffery M.; Usseglio‐Viretta, Francois L. E.; Chinnam, Parameswara R.; et al.
Abstract: Charging lithium‐ion batteries (LiBs) in 10 to 15 min via extreme fast‐charging (XFC) is important for the widespread adoption of electric vehicles (EVs). Lately, the battery research community has focused on identifying XFC bottlenecks and determining novel design solutions. Like other LiB components, cathodes can present XFC bottlenecks, especially when considering long‐term battery life. Therefore, it is necessary to develop a comprehensive understanding of how XFC conditions degrade LiB cathodes. The present article reviews relevant cathode‐focused studies and summarizes the current understanding regarding cathode performance and aging issues under XFC conditions. Dominant aging modes and mechanisms are identified at different length‐scales with electrochemical correlations for LiNi x Mn y Co z O2 (NMC)‐based cathodes. A range of electrochemical techniques and models provide key insights into cathode performance and life issues. A suite of multimodal and multiscale microscopy and X‐ray techniques is surveyed to quantify chemical, structural, and crystallographic NMC‐cathode degradation. Cathode cycle‐life is scaled to equivalent EV miles to illustrate how cathode degradation translates to real‐world scenarios and quantifies cathode‐related bottlenecks that hinder XFC adoption. Finally, the article discusses several cathode cycle‐life aging mitigation strategies with example case studies and identifies remaining challenges. Abstract : The current understanding of cathode performance and aging issues under fast charging conditions is summarized, mitigation strategies are discussed, and remaining challenges identified.